The Study Protocol of “Pharmaceutico Analytical and in Vitro Antimicrobial Activity of Gunjadya Taila Prepared by Using Murchchhita and Amurchchhita Tila Taila” - Gunja K. Dahikar1 , Bharat Rathi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: In this modern era life is full of glamour and faced many health related problem. In modernscience there are huge numbers of drugs said for treatment of diseases but these drugs get resistance to thatparticular disease. Traditionally medicinal plants have been used for many years as topical and internaladministration in the treatment of fungal and bacterial diseases. In Rastarangini Gunjadya Taila mentionedin Kushta and Kandu. In Ayurveda all skin diseases are involved in Kushta Roga. Skin diseases mainly causedby microorganism as per modern science such as Staphylococcus aureus, streptococci and Candidiaalbicanetc. Hence to provide scientific data and statistical validation the study on pharmaceutical analysis and invitro antimicrobial activity of Gunjadya Taila prepared by Murchchhita and Amurchchhita Tila Taila isundertaken.Objective: To study antimicrobial activity of Gunjadya Taila prepared by using Murchchhita andAmurchchhita Tila Taila.Material and Method: Gunjadya Taila will be prepared in Rasashastra department by two method onewith Murchchhita Tila Taila and other with by using Amurchchhita Tila Taila. The prepared drug GunjadyaTaila will be evaluated for organoleptic characters and physicochemical parameters. Gunjadya Taila willbe assessed for antimicrobial effect on gram positive bacteria,gram negative bacteria and fungal group.Inhibition of microbial growth will be investigated by diffusion method.Observation and Results: The data will be assessed for its antimicrobial and antifungal effects by usingANOVA test & unpaired ‘t’ test.Conclusion: This research work on Gungadyataila will show all analytical parameters within range andsignificant effects on gram positive and gram negative bacteria.